Establishment Of Anthocyanin-Producing Callus Culture Of Taraxacum Officinale F. H. Wigg (Asteraceae) - Chong, Sin Yee (2020)
Taraxacum officinale (T. officinale) is a medicinal plant distributed in the areas with temperate climate. Anthocyanin compound present in the petiole of this plant is a potential source of food colouring. Current study focuses on the effect of different factors on anthocyanin accumulation of T. officinale callus. Effect of explant type on callus induction was evaluated on Murashige and Skoog (MS) medium enriched with 0.5 mg/L 1-naphthaleneacetic acid (NAA). Effects of different parameters (NAA concentration, inoculum size, type of basal medium, medium strength, total nitrogen, carbon source and sugar level) were also investigated accordingly. Light microscopy and transmission electron microscopy (TEM) of fresh callus as well as paper chromatography (PC) and ultra performance liquid chromatography (UPLC) of anthocyanin were also carried out. Results demonstrated that root explants had the highest callus induction value (100%) with the formation of friable and purple calli. Pigmented and non-pigmented callus lines were established by selective and repeated subcultures at four-week intervals. Callus growth showed a typical sigmoidal curveand peaked at 35th day on dry cell weight basis.